In search of small active molecules - Crouse, Karen Anne (Universiti Putra Malaysia Press, 2009)
Developments in bioinorganic chemistry, in particular the "discovery by Rosenberg in the late 1960s that a simple complex of platinum could be used in the treatment of Cancer, led to a resurgence in interest in metal complexes. The search for other small complexes that would be selective, effective and cause fewer side-effects has been intensive over the last several decades. A series of several S-substituted dithiocarbazates, hundreds of their Schiff bases and their transition and non-transition metal complexes have been synthesized and characterized in our work. Variation of substituent groups on the dithiocarbazato backbone and use of different metals in their complexation produced small compounds with major differences in structure and coordination. Large variations In biological activity and selectivity have been observed even though the changes in the structure and/or orientation of substituent groups have been specifically designed to be minor, Such small variations enable meaningful application of statistical methods (including QSAR and TSAR, for example) and computational chemistry techniques to the study of the structure- reactivity relationships. A deeper understanding of the action of these compounds gained through these techniques is expected to lead to advances in the design of bioactive compounds.